Role of the Outer Inflammatory Protein A/Cystine–Glutamate Transporter Pathway in Gastric Mucosal Injury Induced by Helicobacter pylori. Issue 5 (26th May 2020) - Du, Jie; Li, Xiao-Hui; Liu, Fen; Li, Wen-Qun; Gong, Zhi-Cheng; Li, Yuan-Jian
Abstract : INTRODUCTION: Helicobacter pylori infection is a major cause of gastrointestinal diseases. However, the pathogenesis of gastric mucosal injury by H. pylori remains unclear. Exogenous glutamate supplementation protects against gastric mucosal injury caused by H. pylori . Previously, we showed that aspirin-induced gastric injury is associated with reduction in glutamate release by inhibition of cystine–glutamate transporter (xCT) activity. We hypothesized that the xCT pathway is involved in H. pylori -induced gastric mucosal injury. In this study, we tested the activity of xCT and evaluated the regulatory effect of outer inflammatory protein (Oip) A on xCT in H. pylori -induced gastric mucosal injury. METHODS: In the H. pylori -infected mice and cell lines, the activity of xCT and the regulatory effect of microRNA on xCT were tested, and the effect of OipA from H. pylori on xCT activity was observed. RESULTS: The results of in vivo and in vitro experiments showed that H. pylori infection induced gastric mucosal injury. This was accompanied by a reduction in xCT activity, which was attenuated by exogenous glutamate treatment. Furthermore, the expression of miR-30b was upregulated, and miR-30b inhibitors significantly restored xCT activity and gastric mucosal injury caused by H. pylori infection. The OipA, a virulence protein from H. pylori, significantly upregulated the expression levels of miR-30b and inhibited xCT activity. DISCUSSION: OipA plays a significant role in H. pylori -induced gastric mucosal injury, and the effects are mediated by micro30b/xCT pathway.